Between individualisation and tradition: transforming religious authority on German and Polish Christian online discussion forums. Issue 2 (3rd April 2017) - Kołodziejska, Marta; Neumaier, Anna
ABSTRACT: The aim of this paper is to connect the debates on individualisation and mediatisation of religion and transformations of religious authority online on theoretical and empirical basis. The classical and contemporary concepts of individualisation of religion, rooted in the secularisation debate, will be connected with Campbell's [2007. "Who's Got the Power? Religious Authority and the Internet." Journal of Computer-Mediated Communication 12 (3): 1043–1062] concept of four layers of religious authority online. The empirical material consists of a joint analysis of German Christian and Polish Catholic Internet forums. In a transnational comparison, the findings show similar tendencies of individualisation and emerging communities of choice, as well as a lasting significance of textual religious authorities, although different levels of authority are negotiated and emphasised to a varying extent. However, in both cases critique of the Church and religion usually emerges offline, and is then expressed online. While the forums do not have a subversive potential, they facilitate adopting a more independent, informed, and reflexive approach to religion.